Handling of Land Plots That Violate Protected Rice Fields: The Urgency of Law Enforcement and Food Security Protection - Alhakim, Zidan Luqman; Ramli, Asmarani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Soil plays a crucial role in human life and the ecosystem, serving as a source of food, shelter, and regional regulation in Indonesia. Land use is governed by agrarian law, including the regulation of protected agricultural areas. However, violations related to the conversion of protected rice fields pose a significant threat to national food security. This study examines cases of land conversion in Semarang Regency, where land designated for protected rice fields has been misused for residential or commercial purposes, violating government regulations. The aim of this research is to analyze the legal implications of such violations and to provide policy recommendations to the National Land Agency. This research uses the empirical juridical method with a descriptive analytical approach. The results indicate that the conversion of protected rice fields has a detrimental impact on food security, reduces agricultural land, and affects farmers’ welfare. The study emphasizes the need for stronger legal enforcement and effective policy implementation by the National Land Agency to address land conversion issues. This research contributes to the efforts of land protection and the enforcement of agrarian law in Indonesia.